Uptake of iron by Kluyveromyces marxianus DSM 5422 cultivated in a whey‐based medium. Issue 7 (16th May 2018) - Löser, Christian; Haas, Christiane; Liu, Wanqiong; Grahl, Sebastian; Bley, Thomas
Abstract: The ability of Kluyveromyces marxianus for converting lactose into ethyl acetate offers a chance for the economical reuse of whey. Iron plays a significant role in this process as ester synthesis requires a low intracellular iron content, xFe . The iron content in turn is decreased by growth due to cell expansion and increased by iron uptake. Thus, the iron‐uptake rate, ψ, is important for the considered process. Iron uptake by K. marxianus DSM 5422 was studied in aerobic cultivation on a whey‐borne medium with varied initial iron content, in part combined with a feed of iron under intensive growth conditions. A possible precipitation of iron that would pretend iron uptake was verified not to have occurred. Regularly measured dissolved iron concentrations, CFe, L, allowed the xFe and ψ parameters to be obtained by model‐based iron balancing. The achieved data were used for establishing a ψ ( CFe, L, xFe ) model. Mathematical simulations based on this iron‐uptake model reproduced the performed cultivation processes. The created iron‐uptake model allows for a future predictive system to be developed for the optimization of biotechnological ester production.